Platelet activation via PAR4 is involved in the initiation of thrombin generation and in clot elasticity development - Vretenbrant, Karin; Ramström, Sofia; Bjerke, Maria; Lindahl, Tomas L. (Thrombosis and Haemostasis, 2007)
Thrombin is a pivotal enzyme formed in the coagulation cascade and an important and potent platelet activator. The two pro-tease-activated thrombin receptors on human platelets are denoted PARI and PAR4. The physiological relevance of PAR4 is still unclear, as both aggregation and secretion can be accomplished by PARI activation alone. In the present study we have investigated the role of PARs in platelet activation, blood coagulation, clot elasticity and fibrinolysis. Flow cytometry, free oscillation rheometry and thrombin generation measurements were used to analyze blood or platelet-rich plasma from healthy individuals. Maximum PARI activation with the peptide SFLLRN gave fewer fibrinogen-binding platelets with lower mean fluorescent intensity than maximum PAR4 activation with AYPGKF. Inhibition of any of the receptors prolonged clotting times. However, PARI is more important for fibrinolysis; inhibition of this receptor prolonged all the steps in the fibrinolytic process. Clot elasticity decreased significantly when the PAR4 receptor was inhibited. In the thrombin generation measurements, PAR4 inhibition delayed the thrombin generation start and peak, but did not affect the total amount of thrombin generated. PAR I inhibition had no significant impact on thrombin generation. We found that PAR4 is most likely activated by low concentrations of thrombin during the initial phase of thrombin generation and is of importance to the clotting time. Furthermore, we suggest that the PAR4 receptor may have a physiological role in the stabilisation of the coagulum.
Keywords: Blood coagulation; clot elasticity; fibrinolysis; PAR receptors